From Terrain to Classroom: Harnessing Ecotourism Situ Gede for Enhanced Geographic Learning - Elsa Aulia; Desti; Anggraini Fitriani; Aflahatin Nupus; Aura Yuga; Anita Eka Putri (Future Space: Studies in Geo-Education, 2024)
In the realm of regional development, tourism emerges as a vital catalyst, promoting economic growth and employment. This study scrutinizes Tasikmalaya City in West Java, spotlighting Situ Gede, a natural area poised for ecotourism. Managed by the regional culture and tourism office, Situ Gede harmonizes cultural and natural tourism, featuring traditions, pilgrimage, and events. The research aims to dissect ecotourism development in Situ Gede, aligning the analysis with geographic education paradigms. It identifies a confluence of cultural and natural tourism, emphasizing the need for collaborative infrastructure enhancement between government and community. Utilizing a qualitative, descriptive approach, the study gleans data from interviews, field observations, and literature. It engages with visitors, vendors, and managers, revealing Situ Gede's ecotourism potential and advocating for integrated development efforts. This inquiry not only enriches geographical understanding of regional tourism but also guides sustainable ecotourism practices, offering insights for policymakers and educators.